Competition and public service broadcasting: stimulating creativity or servicing capital? - Turner, Simon (2016)
In UK public service broadcasting, recent regulatory change has increased the role of the private sector in television production, culminating in the BBC‟s introduction of „creative competition‟ between in-house and independent television producers. Using the concept of „cognitive variety‟, this paper focuses on the increasing role of the independent sector as a source of creativity and innovation in the delivery of programming for the BBC. The paper shows that the intended benefit of introducing new competencies has been thwarted by, on the one hand, a high level of cognitive proximity between in-house and external producers and, on the other, a conflict in values between the BBC and the independent sector, with many of the larger producers responding to a commercial imperative that encourages creativity in profitable genres, but leaves gaps in other areas of provision. Implications for the literature on communities of practice are noted. Key words: Cognitive Variety; Communities of Practice; Public Service Broadcasting; BBC TelevisionIn UK public service broadcasting, recent regulatory change has increased the role of the private sector in television production, culminating in the BBC‟s introduction of „creative competition‟ between in-house and independent television producers. Using the concept of „cognitive variety‟, this paper focuses on the increasing role of the independent sector as a source of creativity and innovation in the delivery of programming for the BBC. The paper shows that the intended benefit of introducing new competencies has been thwarted by, on the one hand, a high level of cognitive proximity between in-house and external producers and, on the other, a conflict in values between the BBC and the independent sector, with many of the larger producers responding to a commercial imperative that encourages creativity in profitable genres, but leaves gaps in other areas of provision. Implications for the literature on communities of practice are noted.